Development of Mathematics Learning Modules Using Project Based Learning Models on the Subjects of the Junior High School Association - Hutapea, Megawati (Jurnal Riset Ilmu Pendidikan, 2022)
The purpose of this study is as follows to find out how the development of learning modules on set material using the Project Based Learning model for class VII SMP students. To find out how the feasibility of developing learning modules on set material is by using a project-based learning model for class VII SMP students. This type of research is research and development (Research and Development) which starts from the analysis, design, to the development or production stage. This study used a questionnaire instrument for the feasibility of the mathematics learning module which was compiled using a Likert scale. Data was collected using a module feasibility analysis instrument which includes content quality, coverage accuracy, project-based learning, display, and language. Based on the results of data analysis, the average module value is 3.18 with good criteria and the average percentage of module eligibility reaches 80% with proper criteria, so that the learning module on the set material using the project-based learning model for class VII SMP students can be used. as a mathematics teaching material